Le vernis des apparences - Grazia Nicosia (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The purpose of this article is to understand the semiotic impact of the cleaning of a painting and the cognitive effects induced on the observer. This study analyses conjointly the visual phenomenon generated by yellowing varnish and its removal and controlled interviews of observers.The removal of yellowing varnish modifies considerably the perception of the picture. Daytime, climate, season and characters activities are modified. The patina may be perceived either as an obstacle to the painting exploration, or, for those who appreciate it, as a medium for a closer relationship between the painting and the observer.